The Effect of Education with Poster Media on the Knowledge of School-Age Children about Healthy Eating Patterns at SDN X Palangka Raya - Sriayu, Pini; Diang Mahalia, Lamia; Mashar, Harlyanti Muthma’innah (Formosa Journal of Science and Technology, 2024)
Primary school-age children with a good healthy diet will have a good nutritional status. Elementary school-age children are one of the groups that are very prone to malnutrition. Based on a preliminary study conducted at SDN X Palangka Raya on 10 students, there were 5 students (50%) who experienced nutritional problems with 3 categories of thinness and 2 categories of obesity. Therefore, it is important to provide education related to healthy eating patterns early on to children. One of the media that can be used to provide education is posters. The purpose of this study was to analyze the effect of education using poster media on the knowledge of school-age children about healthy eating patterns. This is a quasi experimental study with one group pretest and posttest design. The subjects in this study were class V students totaling 37 people. The data obtained were statistically analyzed using the Wilcoxon test.  There was an increase in knowledge after being given education with poster media as much as 40,54% including the good category and 54,06% including the sufficient category. Statistical analysis showed that there was an effect of education using poster media on students' knowledge about healthy eating patterns (p = 0,00).